Circumscribed palmoplantar hypokeratosis: report of two brazilian cases - Lilian Kelly Rocha; Marcello Menta Simonsen Nico (Anais Brasileiros de Dermatologia, 2013)
Circumscribed palmoplantar hypokeratosis is a recently recognized dermatosis and rarely reported. It was first described in 2002 and is characterized by localized loss of the horny layer in the palmoplantar area. This dermatosis is clinically presented with a sharply circumscribed, reddish and asymptomatic plaque with slightly depressed surface localized on the palms or the soles. The clinical differential diagnosis includes mainly porokeratosis and Bowen's disease. Its pathogenesis remains unknown, but studies have proposed a human papillomavirus induced disease or a localized keratinization disorder in the palmoplantar area. We report herein two cases of patients with lesions clinically and microscopically compatible with the diagnosis of circumscribed palmoplantar hypokeratosis. We also present a brief literature review of the etiopathogenic hyphoteses of this dermatosis.